2008
DOI: 10.1136/gut.2007.140871
|View full text |Cite
|
Sign up to set email alerts
|

Tauroursodeoxycholic acid exerts anticholestatic effects by a cooperative cPKC -/PKA-dependent mechanism in rat liver

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 44 publications
5
59
0
Order By: Relevance
“…7 Advances have been made in understanding the mechanisms and sites of action of ursodeoxycholic acid (UDCA) in the therapy of chronic cholangiopathies. 45,46 Our data might emphasize its putative beneficial action as a hepatocyte 47,48 and cholangiocyte 49,50 HCO À 3 secretagogue, particularly for small intrahepatic bile ductules affected in PBC. Our data may also explain, in part, the superiority of norUDCA above UDCA in the treatment of experimental cholangiopathy in Mdr2 À/À mice, a disease affecting also medium-and large-sized ducts, such as PSC 51 : Exogenous norUDCA has been shown to represent the strongest biliary HCO À earlier described for melanoma cells, 29 thus contributing to the biliary HCO À 3 umbrella to prohibit apolar hydrophobic bile acids from entering the cell.…”
Section: Discussionmentioning
confidence: 69%
“…7 Advances have been made in understanding the mechanisms and sites of action of ursodeoxycholic acid (UDCA) in the therapy of chronic cholangiopathies. 45,46 Our data might emphasize its putative beneficial action as a hepatocyte 47,48 and cholangiocyte 49,50 HCO À 3 secretagogue, particularly for small intrahepatic bile ductules affected in PBC. Our data may also explain, in part, the superiority of norUDCA above UDCA in the treatment of experimental cholangiopathy in Mdr2 À/À mice, a disease affecting also medium-and large-sized ducts, such as PSC 51 : Exogenous norUDCA has been shown to represent the strongest biliary HCO À earlier described for melanoma cells, 29 thus contributing to the biliary HCO À 3 umbrella to prohibit apolar hydrophobic bile acids from entering the cell.…”
Section: Discussionmentioning
confidence: 69%
“…Additionally, cholestatic stimuli also induce Mrp2 retrieval from the canalicular membrane, including estradiol-17b-D-glucuronide, taurolithocholate (TLC), and taurochenodeoxycholate (Mottino et al, 2002;Rost et al, 2008;Schonhoff et al, 2013). Conversely, choleretic stimuli such as taurodeoxycholic acid and tauroursodeoxycholic acid can activate Mrp2 insertion back into the canalicular membrane, in a cAMP-regulated process (Beuers et al, 2001;Schonhoff et al, 2008;Wimmer et al, 2008). Mrp2 mislocalization by oxidative stress is similarly reversible by replenishment of GSH and may even be prevented by antioxidants (Sekine et al, 2008(Sekine et al, , 2010.…”
Section: Introductionmentioning
confidence: 95%
“…We have recently reported that the internalization of Abcc2 induced by oxidative stress is regulated by novel PKC (nPKC) in rat liver (Sekine et al, 2006), whereas Kubitz et al (2001) reported that activation of PKC by phorbol ester caused redistribution of ABCC2/Abcc2 from the bile canalicular (apical) membrane to the sinusoidal (basolateral) membrane in a human hepatoma cell line and in rat liver accompanied by cholestasis. Indeed, Abcc2 is known to be phosphorylated by PKC␣ [one of the conventional PKC (cPKC) family] and PKC (nPKC) in vitro Wimmer et al, 2008). Despite growing evidence showing the contribution of PKCs to the post-translational regulation of Abcc2 in hepatocytes, little is known about whether it holds true for other tissues.…”
mentioning
confidence: 99%